Rubella in Orkney: seroepidemiology and vaccination - Moffat, Margaret A. J. (1977)
Rubella haemagglutination inhibiting (HAI) antibody titres were determined in 54 seronegative women and 31 naturally immune women after vaccination and revaccination with Wistar RA27/3 strain rubella vaccine administered by the intranasal or subcutaneous routes or revaccination with the Cendehill strain administered subcutaneously. In addition, HAI antibody titres were determined in 46 seronegative schoolgirls after vaccination with the Cendehill strain and revaccination with the RA27/3 strain. All seronegative women vaccinated with the RA27/3 strain developed antibody, peak titres being reached 6 weeks after vaccination. Six months after vaccination with the Cendehill strain, 45 (98%) of the 46 seronegative girls had developed antibody, but 11 (24%) had not reached their peak titre by 6 weeks, suggesting a slower response than that elicited by the RA27/3 strain. Revaccination did not induce significant antibody responses in the seronegative women vaccinated 6 months previously with RA27/3 but 4 naturally immune women developed an eightfold increase in antibody. In 10 (22%) of 46 schoolgirls previously vaccinated with the Cendehill strain a significant rise in antibody followed revaccination with RA27/3. These results provide further evidence of the more rapid antibody responses elicited by the RA27/3 vaccine in comparison with the Cendehill vaccine. An outbreak of natural rubella occurred in 1972 and 97 cases were confirmed serologically. The clinical disease was more common in older school-children and in adults. More males than females were affected in the 11-15 age group, the sex ratio being 18:12; this may be explained by the routine vaccination of girls of this age group as part of the national programme which began in 1970. The significance of the persistence of high HAI antibody titres after natural infection and the effect of the epidemic on the serological status of the population are discussed.